Peoples’ Perception on Decentralized Agri Service Provision at Local Level: A Case of Lamjung District, Nepal - Karki, Sabin; Jaishi, Mahesh; Chapagain, Arjun (International Journal of Social Sciences and Management, 2018)
Perceptions are the attitudes of people which are considered as critical components of socio-cultural context. Decentralization promotes equity, people’s participation and effective service delivery at the local level through transfer of responsibilities and competencies, capacities and resource allocation power to a lower level of government. This also implies in the agricultural sector. In this context, a research was designed to study the attitudes of extension workers and farmers on decentralized agriculture service system in 3 Municipalites and 3 Village Development Committees (VDCs) of Lamjung district. Using by stratified proportionate sampling method, we selected 60 respondents, out of which 41.67 percent were the farmers and 58.33% were the extension workers. Five point Likert scales were developed to measure perception regarding four major components of decentralization. Qualitative as well as quantitative data were analyzed. Focus Group Discussion was also conducted to identify the problems. The result showed that, regarding the planning component, fiscal component and implementation component majority of respondent perceive positive response, while the perception of structural component was found varied response. Further findings indicated that there was lack of clear ideas on well-functioning of process among extension workers and farmers. Moreover, result showed that implementation related was the 1st ranked problem followed by financial related and structural related. Structural change to address increasing farmers' demand was one of the key interventions suggested by the respondents for the effectiveness of decentralized agriculture service provision Int. J. Soc. Sc. Manage. Vol. 5, Issue-4: 243-249